Strategy for Developing Pedagogical and Professional Competence of Islamic Education Teachers Through Integrated Training Management - Sugarto Nasarudin; Andi Markarma; Gusnarib; Nasrul (At Turots: Jurnal Pendidikan Islam, 2026)
This research aims to analyze integrated training management strategies in improving the pedagogical and professional competencies of Islamic Religious Education (PAI) teachers. The gap between mastery of material substance (professional) and methodological proficiency (pedagogical) in the digital era is the main background for the need for an integrative HR development approach. The research method used is descriptive qualitative. Data were collected through in-depth interviews with principals and teachers, participatory observation of training activities and teaching practices, and documentation studies. Data analysis applied an interactive model including data reduction, data presentation, and drawing conclusions. The research results show that integrated training management is implemented through four strategic stages: 1) Planning based on need analysis through honest competency audits to develop an integrative curriculum; 2) Implementation using blended methods and a learning by doing approach that combines theory and practice simultaneously through microteaching; 3) Integration of information technology using the Learning Management System (LMS) as a catalyst to unify professional content with digital pedagogy; and 4) Post-training evaluation through clinical supervision and peer review reflection forums. This research concludes that combining pedagogical and professional aspects in a continuous training cycle can change the teacher's teaching paradigm to be more student-centered and ensure that teacher competencies are effectively implemented to improve the quality of classroom learning